Extração e análise do óleo de moringa oleifera Lam. proveniente de quatro estados do Nordeste Brasileiro - Chaves, Josyelem Tiburtino Leite (2017)
Lipids are the main components of human’s diet for its high energy production. This class of chemical compounds form the oils originated from oil seeds. The vegetable oils, in the last years, have been gained larger proportions due to its various characteristics and uses. Many plants have oilseeds, among them, Moringa oleifera (Lam.) that has high content of oil and multiple uses. After the exposed, it was objected in this chapter to do a literature review about the vegetable oil of Moringa oleifera, the extraction methods and the characteristics to being determinate on oil and seeds. The term seed is utilized when talking about mature ovule, food reserve material and integument. Seeds are classified by their chemical composition, to that ones that have lipids as main reserve substance is given the name of oilseeds. This seeds have vegetable oil, products constituted of a mixture of triglycerides and that can be used in industry. The moringa (Moringaceae), plant oilseed, has an enormous variety of uses and this fact has attracted many researchers, it can to bear fruit in its first year in the ideal conditions of management and has 17 a 40% of oil. The extraction of this vegetable oil can occur by pressing or with a solvent. The oil analysis has an extreme importance to know the oil characteristics. The chemical/centesimal composition determines characteristics like humidity, greys and protein. The chemical composition of the oil determines which fatty acids the vegetable oil is formed, oil state of conservation, saponification potentiality, density and others. The oil composition can variate due to climatic conditions and agronomic, quality of feedstock and extraction methods.